2018
DOI: 10.1038/s41598-018-21255-7
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Against Lawsonia intracellularis Decreases Shedding of Salmonella enterica serovar Typhimurium in Co-Infected Pigs and Alters the Gut Microbiome

Abstract: Salmonella enterica serovar Typhimurium continues to be a major cause of foodborne illness worldwide and pork can serve as a source of infection. Co-infection of S. enterica with Lawsonia intracellularis, a common intestinal pathogen of swine, has been found as risk factor for increased S. enterica shedding. The objective of this study was to investigate if vaccination against L. intracellularis could lead to decreased S. Typhimurium shedding. To test this hypothesis, pigs were challenged with either S. Typhim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 49 publications
9
36
0
3
Order By: Relevance
“…It is now acknowledged that L. intracellularis infection is common in weaned pigs ( 2 ). It is also known that L. intracellularis infection leads to changes in the pig gut microbiome, indicating a complex association ( 70 , 90 , 91 ). Early studies show that experimental infection of pigs with a cell culture propagated pure L. intracellularis inoculum does not cause disease in gnotobiotic pigs but the same inoculum produces disease in conventional pigs ( 12 ).…”
Section: Control Of L Intracellularismentioning
confidence: 99%
“…It is now acknowledged that L. intracellularis infection is common in weaned pigs ( 2 ). It is also known that L. intracellularis infection leads to changes in the pig gut microbiome, indicating a complex association ( 70 , 90 , 91 ). Early studies show that experimental infection of pigs with a cell culture propagated pure L. intracellularis inoculum does not cause disease in gnotobiotic pigs but the same inoculum produces disease in conventional pigs ( 12 ).…”
Section: Control Of L Intracellularismentioning
confidence: 99%
“…However, it cannot be ruled out that the vaccination itself has a protective effect. Vaccination against L. intracellularis at three weeks of age significantly reduced S. Typhimurium shedding ( p < 0.05) in co-infected animals in comparison to the co-infected group without vaccination and the group challenged with S. Typhimurium alone [ 41 ]. Twenty-one days post vaccination, the animals were challenged with a pure culture of L. intracellularis (2 × 10 9 organisms per pig; strain PHE/MN1-00).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one days post vaccination, the animals were challenged with a pure culture of L. intracellularis (2 × 10 9 organisms per pig; strain PHE/MN1-00). One week post- L. intracellularis challenge, the pigs were challenged orally with S. Typhimurium (strain 798; 1 × 10 8 organisms per pig) [ 41 ]. At seven days post-infection, the co-challenged non-vaccinated group shed 2.94 log 10 S. Typhimurium organisms per gramme faeces, while the vaccinated co-challenged group shed 0.82 log 10 S. Typhimurium organisms per gramme faeces ( p = 0.003) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that LI infection is a risk factor for fecal shedding of Salmonella Typhimurium (ST) in affected pigs [ 4 ]. It has been reported that colonization and shedding of ST significantly increased in pigs experimentally co-infected with LI and ST [ 5 ]. This supports the hypothesis that both pathogens have indirect interactions that might be mediated by pre-disposing organisms, resulting in underlying changes in the composition of the intestinal microbiome [ 6 ].…”
Section: Introductionmentioning
confidence: 99%